2018
DOI: 10.1136/bmjdrc-2018-000587
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotyping of newly diagnosed type 2 diabetes in Yemen

Abstract: ObjectiveTo identify clinical phenotypes of type 2 diabetes (T2D) among adults presenting with a first diagnosis of diabetes.Research design and methodsA total of 500 consecutive patients were subject to clinical assessment and laboratory investigations. We used data-driven cluster analysis to identify phenotypes of T2D based on clinical variables and Homeostasis Model Assessment (HOMA2) of insulin sensitivity and beta-cell function estimated from paired fasting blood glucose and specific insulin levels.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…Our data are far from conclusive, but we can say that studying the features of T2D in a population made of western residents and undocumented migrants, we obtained distinct clusters of disease phenotypes. This is not different from what was observed by other researchers in more homogeneous populations [3,4]. This clustering appeared to be at least partially independent from racial/ethnical factors.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Our data are far from conclusive, but we can say that studying the features of T2D in a population made of western residents and undocumented migrants, we obtained distinct clusters of disease phenotypes. This is not different from what was observed by other researchers in more homogeneous populations [3,4]. This clustering appeared to be at least partially independent from racial/ethnical factors.…”
Section: Discussioncontrasting
confidence: 53%
“…Type 2 diabetes (T2D), on the contrary, appears to represent a wide spectrum of metabolic disorders sharing chronic hyperglycaemia as a common feature. It is now clear that a classification more respondent to precision medicine criteria is needed, and attempts have been made to group T2D patients into different homogenous clusters [3,4]. This need for a better understanding of T2D phenotypes has practical implications for the pharmacological treatment of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests current classifying method has, at least partly, captured their heterogeneities among diabetic patients. Also, compared to BMI, waist circumference shows a similar distribution and equivalent effect sizes among T2D sub-phenotypes, indicating that including both BMI and waist circumference as cluster variables in the study might be information redundancy ( 23 , 24 ). However, the HDL level was much less distinct among different diabetes sub-phenotypes.…”
Section: Discussionmentioning
confidence: 91%
“…However, even in patients with a short duration of T2DM, a severe decrease in beta cell function can often be observed. [26,27] Considering these individual differences, there is a limit to predicting the long-term outcome of glycemic control only by the duration of diabetes. Nannipieri et al reported that T2DM remission after RYGB depends on the initial degree of beta cell dysfunction in morbidly obese individuals, [28] and it is not fully clear whether similar results could be expected in patients with gastric cancer with a relatively lean state.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in patients with a short duration of T2DM, a severe decrease in beta cell function can often be observed. [26,27] Considering these individual differences, there is a limit to predicting the long-term outcome of glycemic control only by the duration of diabetes.…”
Section: Discussionmentioning
confidence: 99%